Positive electrode active material, positive electrode, lithium-ion secondary battery, and lithium-ion secondary battery module
Patent Information
- Application Number
- JP2025058535
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0008】 本発明によれば、ガスの発生を抑制できるリチウムイオン二次電池を得ることが可能な正極活物質、ガスの発生を抑制できるリチウムイオン二次電池を得ることが可能な正極、並びに、ガスの発生を抑制できるリチウムイオン二次電池およびリチウムイオン二次電池モジュールを提供することができる。
Smart Images

Figure 2026165894000002 
Figure 2026165894000001
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material, a positive electrode, a lithium ion secondary battery, and a lithium ion secondary battery module.
Background Art
[0002] Lithium composite oxides are known as positive electrode active materials for lithium ion secondary batteries. Examples of the technology of lithium ion secondary batteries using a lithium composite oxide as the positive electrode active material include those described in Patent Document 1.
[0003] Patent Document 1 discloses a positive electrode active material for lithium secondary batteries comprising at least one secondary particle which is an aggregate of primary giant particles, wherein the average particle diameter (D50) of the primary giant particles is 1 μm or more, part or all of the surfaces of the secondary particles or the primary giant particles are coated with a lithium boron oxide, the average particle diameter (D50) of the secondary particles is 3 to 15 μm, and the specific surface area of the positive electrode active material before rolling the electrode containing the positive electrode active material is 0.2 to 1.25 m 2 / g, the BET change rate of the positive electrode active material before and after rolling the electrode containing the positive electrode active material is 70% or less, and the rolling condition for the electrode is a condition that the porosity of the electrode is 15 to 30%, is described as a positive electrode active material for lithium secondary batteries. And Patent Document 1 describes that it is possible to control the BET change during the rolling process and provide a positive electrode active material with an improved capacity retention rate.
Related Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of Invention
Problems to be Solved by the Invention
[0005] The present invention provides a positive electrode active material capable of producing a lithium-ion secondary battery that can suppress gas generation, a positive electrode capable of producing a lithium-ion secondary battery that can suppress gas generation, and a lithium-ion secondary battery and a lithium-ion secondary battery module that can suppress gas generation. [Means for solving the problem]
[0006] The inventors diligently conducted research to achieve the above objectives. As a result, they discovered that by limiting the number of microcracks in the positive electrode active material after compression to a predetermined range, it is possible to obtain a positive electrode active material that can suppress gas generation, thus completing the present invention.
[0007] [1] A positive electrode active material for lithium-ion secondary batteries, A positive electrode active material having a number of microcracks after compression, measured by the following method (Method 1), of 2.0 or less. (Method 1) The positive electrode active material is placed in a mold, and the density is 3.7 g / cm³. 3 The material is compressed to the following state. The compressed positive electrode active material is observed by SEM at a magnification of 5000x, and the number of microcracks within a 10 μm × 10 μm area is measured from the image obtained. The number of microcracks within a 10 μm × 10 μm area is measured at 10 different locations on the compressed positive electrode active material, and the average value of the microcrack counts at the 10 locations is taken as the number of microcracks after compression. [2] The positive electrode active material according to [1], wherein the number of nanoparticles after compression of the positive electrode active material, as measured by the following (Method 2), is 10.0 or less. (Method 2) The positive electrode active material is placed in a mold, and the density is 3.7 g / cm³. 3compress to achieve the state. From the image obtained by performing SEM observation on the compressed positive electrode active material at a magnification of 5000 times, the number of nanoparticles with a maximum diameter of 10 nm or more and 50 nm or less adhering to the surface of the positive electrode active material within a range of 10 μm × 10 μm is measured. The number of the nanoparticles within a range of 10 μm × 10 μm is measured at 10 different locations of the compressed positive electrode active material, and the average value of the number of the nanoparticles at the 10 locations is defined as the number of nanoparticles after compression. [3] The average particle diameter D in the volume-based particle size distribution of the positive electrode active material measured by a laser diffraction scattering particle size distribution measurement method 50 is 0.5 μm or more and 15.0 μm or less, the positive electrode active material according to [1] or [2]. [4] The particle diameter D at which the cumulative value in the volume-based particle size distribution of the positive electrode active material measured by a laser diffraction scattering particle size distribution measurement method is 10% 10 , the particle diameter D at which the cumulative value is 90% 90 and the average particle diameter D 50 calculated from (D 90 -D 10 ) / D 50 has a value of 0.50 or more and 2.00 or less, the positive electrode active material according to any one of [1] to [3]. [5] The particle diameter D at which the cumulative value in the volume-based particle size distribution of the positive electrode active material measured by a laser diffraction scattering particle size distribution measurement method is 10% 10 is 0.1 μm or more and 10.0 μm or less, the positive electrode active material according to any one of [1] to [4]. [6] The particle diameter D at which the cumulative value in the volume-based particle size distribution of the positive electrode active material measured by a laser diffraction scattering particle size distribution measurement method is 90% 90 is 1.0 μm or more and 25.0 μm or less, the positive electrode active material according to any one of [1] to [5]. [7] Comprising single crystal particles composed of a lithium composite oxide (X), the positive electrode active material according to any one of [1] to [6]. [8] The positive electrode active material according to [7], wherein the lithium composite oxide (X) comprises one or more composite oxides selected from the group consisting of lithium-nickel composite oxides, lithium-cobalt composite oxides, lithium-nickel-aluminum composite oxides, and lithium-nickel-cobalt-manganese composite oxides. [9] The positive electrode active material according to [7] or [8], wherein the lithium composite oxide (X) comprises a lithium-nickel-cobalt-manganese composite oxide.
[10] A positive electrode active material according to any one of [7] to [9], wherein, when the total amount of metallic elements other than lithium contained in the lithium composite oxide (X) is taken as 100 mol%, the nickel content is 80 mol% or more.
[11] A positive electrode active material according to any of [1] to
[10] , wherein the volume change rate is 120% or less, as determined by the method described below (Method 3). (Method 3) A mixture consisting of 97.5 parts by mass of the positive electrode active material, 1.0 part by mass of MWCNT (multi-walled carbon nanotube), and 1.5 parts by mass of PVDF (polyvinylidene fluoride) is to be mixed with an appropriate amount of water to prepare a positive electrode active material slurry. Next, the positive electrode active material slurry is applied to aluminum foil, which is the positive electrode current collector, to achieve an initial charge capacity of 4.2 mAh / cm² per unit area. 2 After applying the coating in an amount such that the positive electrode active material layer has a density of 3.7 g / cm³, the positive electrode laminate is obtained. Next, using a roll press machine, the positive electrode laminate is processed so that the density of the positive electrode active material layer is 3.7 g / cm³. 3The positive electrode is obtained by pressing with a pressure such that the positive electrode and the negative electrode containing a mixture of graphite and Si-C composite particles are arranged opposite each other via a polyethylene separator, and the electrode laminate and non-aqueous electrolyte are placed in a laminate casing molded from a film mainly composed of aluminum, and a positive electrode tab and a negative electrode tab are connected to the negative electrode and the positive electrode, respectively, and the periphery of the laminate casing is sealed to produce a lithium-ion secondary battery. The obtained lithium-ion secondary battery is placed in a constant temperature bath at 45°C and charged at 30mA until the upper limit voltage reaches 4.2V, at which point it is charged at a constant voltage until the total charging time is 2.5 hours. Next, it is discharged at a constant current of 30mA until the lower limit voltage reaches 2.5V. Then, this charge-discharge cycle is repeated 750 times, and the volume change rate is calculated from the volume of the lithium-ion secondary battery after 750 charge-discharge cycles and the volume of the lithium-ion secondary battery after 2 charge-discharge cycles.
[12] A positive electrode containing the positive electrode active material described in any of [1] to
[11] .
[13] A lithium-ion secondary battery having the positive electrode described in
[12] .
[14] A lithium-ion secondary battery module comprising the lithium-ion secondary battery described in
[13] . [Effects of the Invention]
[0008] According to the present invention, it is possible to provide a positive electrode active material that can produce a lithium-ion secondary battery that can suppress gas generation, a positive electrode that can produce a lithium-ion secondary battery that can suppress gas generation, and a lithium-ion secondary battery and a lithium-ion secondary battery module that can suppress gas generation. [Brief explanation of the drawing]
[0009] [Figure 1] This is a schematic cross-sectional view illustrating an example of a lithium-ion secondary battery according to this embodiment. [Modes for carrying out the invention]
[0010] Embodiments of the present invention will be described below with reference to the drawings. In all drawings, similar components are denoted by the same reference numeral, and explanations are omitted where appropriate. Furthermore, the drawings are schematic and do not necessarily correspond to actual dimensional proportions. In the specification, unless otherwise specified, the notation "A to B" regarding a numerical range means A or greater and B or less. For example, 1 to 5% means 1% or greater and 5% or less.
[0011] <Cathode active material> The positive electrode active material of this embodiment is a positive electrode active material for a lithium-ion secondary battery, wherein the number of microcracks after compression of the positive electrode active material, as measured by the following (Method 1), is 2.0 or less. (Method 1) The positive electrode active material is placed in a mold, and the density is 3.7 g / cm³. 3 The material is compressed to the following state. The compressed positive electrode active material is observed by SEM at a magnification of 5000x, and the number of microcracks within a 10 μm × 10 μm area is measured from the image obtained. The number of microcracks within a 10 μm × 10 μm area is measured at 10 different locations on the compressed positive electrode active material, and the average value of the microcrack counts at the 10 locations is taken as the number of microcracks after compression.
[0012] The inventors of this invention have found a correlation between the number of microcracks in the positive electrode active material after compression and the gas generation of the resulting lithium-ion secondary battery. Based on this finding, the inventors conducted further intensive studies and found that by reducing the number of microcracks in the positive electrode active material after compression to below the above upper limit, the amount of gas generated in the resulting lithium-ion secondary battery can be reduced, thus completing the present invention. Although it is not clear why keeping the number of microcracks in the compressed positive electrode active material below the above upper limit reduces the amount of gas generated in the resulting lithium-ion secondary battery, it is thought that keeping the number of microcracks in the compressed positive electrode active material below the above upper limit suppresses cracking and pulverization of the positive electrode active material during the manufacturing process and charging / discharging of the lithium-ion secondary battery. This suppresses the reaction between the positive electrode active material and the electrolyte, which is considered to be one of the causes of gas generation during the charge-discharge cycle, thereby reducing the amount of gas generated in the lithium-ion secondary battery.
[0013] The number of microcracks in the positive electrode active material after compression in this embodiment is 2.0 or less, preferably 1.5 or less, and more preferably 1.0 or less, from the viewpoint of suppressing gas generation in the resulting lithium-ion secondary battery. The lower limit of the number of microcracks in the positive electrode active material after compression in this embodiment is not particularly limited, but may be 0.0 or more, 0.1 or more, or 0.3 or more.
[0014] From the viewpoint of further suppressing gas generation in the lithium-ion secondary battery obtained, the number of microcracks in the positive electrode active material after compression in this embodiment is preferably 0.0 to 2.0, and may also be 0.1 to 1.5, or 0.3 to 1.0. The number of microcracks in the positive electrode active material after compression can be adjusted by controlling the types and ratios of constituent elements of the positive electrode active material, firing conditions, grinding conditions, classification conditions, and the presence or absence of a coating layer.
[0015] In this embodiment, from the viewpoint of further suppressing gas generation in the resulting lithium-ion secondary battery, the number of nanoparticles after compression of the positive electrode active material, as measured by the following (Method 2), is preferably 10.0 or less, more preferably 9.0 or less, even more preferably 8.0 or less, and even more preferably 7.0 or less. The lower limit of the number of nanoparticles after compression of the positive electrode active material in this embodiment is not particularly limited, but may be, for example, 0.0 or more, 0.1 or more, 1.0 or more, or 1.5 or more. (Method 2) The positive electrode active material is placed in a mold, and the density is 3.7 g / cm³. 3 Compress it so that it becomes [this]. The number of nanoparticles with a maximum diameter of 10 nm to 50 nm attached to the surface of the positive electrode active material within a 10 μm × 10 μm area is measured from the image obtained by observing the compressed positive electrode active material at a magnification of 5000x. The number of nanoparticles within a 10 μm × 10 μm area is measured at 10 different locations on the compressed positive electrode active material, and the average value of the number of nanoparticles at the 10 locations is taken as the number of nanoparticles after compression.
[0016] In this embodiment, the number of nanoparticles in the positive electrode active material after compression is preferably 0.0 to 10.0, and may also be 0.1 to 9.0, 1.0 to 8.0, or 1.5 to 7.0. The number of nanoparticles after compression of the positive electrode active material can be adjusted by adjusting the types and ratios of constituent elements of the positive electrode active material, firing conditions, grinding conditions, classification conditions, and the presence or absence of a coating layer.
[0017] For the positive electrode active material of this embodiment, the particle size D at which the cumulative value in the volume-based particle size distribution measured by laser diffraction scattering particle size distribution analysis is 10% 10 , particle size D which accounts for 90% 90 and average particle diameter D 50 (D 90 -D 10 ) / D50 The value is preferably 0.50 to 2.00, more preferably 0.60 to 1.80, even more preferably 0.70 to 1.60, even more preferably 0.75 to 1.50, and even more preferably 0.75 to 1.20.
[0018] The average particle diameter D of the positive electrode active material in this embodiment 50 The particle size is preferably 0.5 μm to 15.0 μm, more preferably 1.0 μm to 10.0 μm, even more preferably 2.0 μm to 8.5 μm, and even more preferably 2.5 μm to 7.0 μm.
[0019] The particle size D of the positive electrode active material in this embodiment 10 The particle size is preferably 0.1 μm to 10.0 μm, more preferably 0.5 μm to 8.0 μm, even more preferably 1.0 μm to 6.0 μm, and even more preferably 1.5 μm to 5.0 μm.
[0020] The particle size D of the positive electrode active material in this embodiment 90 The particle size is preferably 1.0 μm to 25.0 μm, more preferably 2.0 μm to 20.0 μm, even more preferably 3.0 μm to 15.0 μm, even more preferably 4.0 μm to 12.0 μm, and even more preferably 5.0 μm to 10.0 μm.
[0021] <Single crystal grains composed of lithium composite oxide (X)> The positive electrode active material of this embodiment preferably includes single crystal particles composed of lithium composite oxide (X). In this embodiment, single-crystal particles are particles in which no grain boundaries are observed when viewed with an electron microscope at 1000 to 5000x magnification, and in which the particle is composed of a single crystal grain. Even if several to several dozen single-crystal particles are closely packed together, they still fall under the category of single-crystal particles. On the other hand, in this embodiment, polycrystalline particles are particles in which multiple crystal grains with different crystal orientations and grain boundaries are observed within the solid when viewed with an electron microscope at 1000 to 5000x magnification.
[0022] From the viewpoint of further suppressing gas generation in the resulting lithium-ion secondary battery, the lithium composite oxide (X) preferably comprises one or more composite oxides selected from the group consisting of lithium-nickel composite oxides, lithium-cobalt composite oxides, lithium-nickel-aluminum composite oxides, and lithium-nickel-cobalt-manganese composite oxides, and more preferably comprises lithium-nickel-cobalt-manganese composite oxides.
[0023] In this embodiment, when the lithium composite oxide (X) in the positive electrode active material includes a lithium-nickel-cobalt-manganese composite oxide, the lithium-nickel-cobalt-manganese composite oxide preferably includes a composite oxide represented by the following formula (1) from the viewpoint of further improving the energy density of the resulting lithium-ion secondary battery.
[0024] Li a Ni b Co c Mn d M e O2(1) In formula (1) above, M is one or more selected from the group consisting of Al, Mg, Na, Co, K, W, Cu, Fe, Ba, V, Cr, Ti, Zr, Zn, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and 0.5≦a≦1.5, 0.6≦b<1.0, 0 <c<0.2、0<d<0.2、0≦e<1.0である。
[0025] In the composite oxide of formula (1) above, 0.5 ≤ a ≤ 1.5, preferably 0.6 ≤ a ≤ 1.4, more preferably 0.7 ≤ a ≤ 1.3, even more preferably 0.8 ≤ a ≤ 1.2, even more preferably 0.9 ≤ a ≤ 1.1, and even more preferably a = 1.0.
[0026] Further, in the composite oxide of the above formula (1), 0.6≦b<1.0, and from the viewpoint of further improving the capacity of the obtained lithium ion secondary battery, b is preferably 0.65≦b<1.0, more preferably 0.7≦b<1.0, still more preferably 0.75≦b<1.0, still more preferably 0.8≦b≦0.97, and still more preferably 0.85≦b≦0.95.
[0027] In the composite oxide of the above formula (1), 0<c<0.2, preferably 0.01≦c≦0.15, more preferably 0.02≦c≦0.15, still more preferably 0.03≦c≦0.1, and still more preferably 0.03≦c≦0.08.
[0028] In the composite oxide of the above formula (1), 0<d<0.2, preferably 0.001≦d≦0.15, more preferably 0.003≦d≦0.1, still more preferably 0.005≦d≦0.08, and still more preferably 0.01≦d≦0.06.
[0029] In the composite oxide of the above formula (1), 0≦e<1.0, preferably 0≦e≦0.5, more preferably 0≦e≦0.3, still more preferably 0≦e≦0.2, still more preferably 0≦e≦0.1, and still more preferably e=0.
[0030] When the total content of metal elements other than lithium contained in the lithium composite oxide (X) in the positive electrode active material of the present embodiment is taken as 100 mol%, the nickel content is preferably 80 mol% or more, more preferably 82 mol% or more, still more preferably 84 mol% or more, still more preferably 86 mol% or more, and still more preferably 88 mol% or more, from the viewpoint of further improving the capacity of the obtained lithium ion secondary battery. The upper limit of the nickel content of the lithium composite oxide (X) is not particularly limited, and may be, for example, 99 mol% or less, 98 mol% or less, 96 mol% or less, or 95 mol% or less.
[0031] The volume change rate of the positive electrode active material in this embodiment, according to the method described below, is preferably 120% or less, more preferably 118% or less, even more preferably 116% or less, and even more preferably 115% or less, from the viewpoint of further suppressing gas generation in the resulting lithium-ion secondary battery. There is no particular limit to the lower limit of the volume change rate of the positive electrode active material in this embodiment, but for example, it may be 100% or more, 102% or more, or 104% or more. (method) A mixture consisting of 97.5 parts by mass of the positive electrode active material, 1.0 part by mass of MWCNT (multi-walled carbon nanotube), and 1.5 parts by mass of PVDF (polyvinylidene fluoride) is to be mixed with an appropriate amount of water to prepare a positive electrode active material slurry. Next, the positive electrode active material slurry is applied to aluminum foil, which is the positive electrode current collector, to achieve an initial charge capacity of 4.2 mAh / cm² per unit area. 2 After applying the coating in an amount such that the positive electrode active material layer has a density of 3.7 g / cm³, the positive electrode laminate is obtained. Next, using a roll press machine, the positive electrode laminate is processed so that the density of the positive electrode active material layer is 3.7 g / cm³. 3 The positive electrode is obtained by pressing with a pressure such that the positive electrode and the negative electrode containing a mixture of graphite and Si-C composite particles are arranged opposite each other via a polyethylene separator, and the electrode laminate and non-aqueous electrolyte are placed in a laminate casing molded from a film mainly composed of aluminum, and a positive electrode tab and a negative electrode tab are connected to the negative electrode and the positive electrode, respectively, and the periphery of the laminate casing is sealed to produce a lithium-ion secondary battery. The obtained lithium-ion secondary battery is placed in a constant temperature bath at 45°C and charged at 30mA until the upper limit voltage reaches 4.2V, at which point it is charged at a constant voltage until the total charging time is 2.5 hours. Next, it is discharged at a constant current of 30mA until the lower limit voltage reaches 2.5V. Then, this charge-discharge cycle is repeated 750 times, and the volume change rate is calculated from the volume of the lithium-ion secondary battery after 750 charge-discharge cycles and the volume of the lithium-ion secondary battery after 2 charge-discharge cycles.
[0032] <Method for producing the positive electrode active material of this embodiment> An example of a method for producing the positive electrode active material of this embodiment will be described in detail. The positive electrode active material of this embodiment includes, for example, the steps of (1) producing composite hydroxide particles of a transition metal, and (2) producing a positive electrode active material using the composite hydroxide particles of a transition metal and a lithium compound. (1) In the process of producing complex hydroxide particles of transition metals, the sulfate or nitrate of the transition metal and an alkaline solution (sodium hydroxide, ammonia, etc.) are placed in a reactor and prepared by coprecipitation. (2) In the step of producing a positive electrode active material using transition metal composite hydroxide particles and a lithium compound, the transition metal composite hydroxide particles and the lithium compound are mixed and calcined in an oxygen atmosphere, and then the resulting calcined powder is mixed with the lithium compound and further calcined in an oxygen atmosphere to obtain the positive electrode active material of this embodiment. It is preferable to perform the step of mixing the resulting calcined powder with the lithium compound and calcining in an oxygen atmosphere multiple times. The reactor used in step (1) can be, for example, a batch reactor or a continuous tank reactor (CSTR), and it is preferable to use a batch reactor.
[0033] Here, by adjusting the particle size of the transition metal composite hydroxide particles and the firing temperature in air, the resulting positive electrode active material particles can be adjusted to be single crystals or polycrystalline, and the particle size can also be controlled. In the case of single-crystal particles, multiple particles aggregate when the particles are grown to a predetermined particle size during the firing process, so single-crystal particles of a predetermined particle size can be obtained by crushing the aggregated particles with a jet mill or ball mill. The positive electrode active material can be classified by sieving it with meshes of different mesh openings and linearities. The steps of crushing and classifying the positive electrode active material are preferably performed after the pre-firing or firing in step (2), and more preferably both after the pre-firing and firing in step (2), from the viewpoint of obtaining positive electrode active material particles with a more suppressed number of microcracks. In the method for producing positive electrode active material of this embodiment, it is preferable to perform the step of crushing the positive electrode active material from the viewpoint of obtaining positive electrode active material particles with a more suppressed number of microcracks, and it is more preferable to combine the steps of crushing and classifying the positive electrode active material. Furthermore, from the viewpoint of adjusting the number of microcracks in the positive electrode active material after compression to an appropriate range, it is preferable to process the calcined powder obtained after calcination using a wet ball mill for 5 hours or more.
[0034] Furthermore, the method for producing the positive electrode active material of this embodiment preferably includes the step of (3) forming a coating layer on the surface of the positive electrode active material by heat-treating a mixture containing the positive electrode active material and a coating material. The coating material preferably contains one or more metal elements selected from the group consisting of Ni, Co, Al, and Zr, more preferably one or more metal elements selected from the group consisting of Ni, Co, and Al, even more preferably one of Ni and Co, and even more preferably one of Co. If the coating material contains Co, it contains one or more elements selected from the group consisting of, for example, Co(OH)2, Co2O3, Co(OH)3, and cobalt acetate, and preferably one of Co(OH)2. Furthermore, the coating material is preferably in powder form from the viewpoint of improving reaction efficiency. In step (3), the heat treatment temperature is, for example, 600°C to 1000°C. Also, in step (3), the heat treatment time is, for example, 5 hours to 24 hours.
[0035] <Positive electrode> The positive electrode of this embodiment includes the positive electrode active material of this embodiment. The positive electrode of this embodiment preferably comprises a positive electrode active material layer containing the positive electrode active material of this embodiment and a positive electrode current collector, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery. The positive electrode active material layer of this embodiment preferably comprises the positive electrode active material and binder of this embodiment, and more preferably comprises the positive electrode active material, binder and conductive additive of this embodiment, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery.
[0036] In this embodiment, the content of the positive electrode active material in the positive electrode active material layer is preferably 50.0 parts by mass or more and 99.9 parts by mass or less, more preferably 75.0 parts by mass or more and 99.5 parts by mass or less, even more preferably 85.0 parts by mass or more and 99.0 parts by mass or less, even more preferably 90.0 parts by mass or more and 98.5 parts by mass or less, and even more preferably 95.0 parts by mass or more and 98.5 parts by mass or less, when the total volume of the positive electrode active material layer is 100.0 parts by mass, in order to further improve the battery performance of the resulting lithium-ion secondary battery.
[0037] In this embodiment, the content of lithium composite oxide (X) in the positive electrode active material layer is preferably 50 parts by mass or more and 100 parts by mass or less, more preferably 60 parts by mass or more and 100 parts by mass or less, even more preferably 70 parts by mass or more and 100 parts by mass or less, even more preferably 80 parts by mass or more and 100 parts by mass or less, even more preferably 90 parts by mass or more and 100 parts by mass or less, even more preferably 95 parts by mass or more and 100 parts by mass or less, and even more preferably 98 parts by mass or more and 100 parts by mass or less, when the content of positive electrode active material in the positive electrode active material layer is 100 parts by mass.
[0038] Examples of conductive additives in the positive electrode active material layer of this embodiment include carbon materials such as carbon fibers such as carbon nanofibers, carbon black such as acetylene black and Ketjenblack, activated carbon, graphite, mesoporous carbon, fullerenes, and carbon nanotubes. From the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, it is preferable to use carbon nanotubes (CNTs). CNTs are materials having a single-wall or multi-wall coaxial tube structure of a six-membered ring network of carbon atoms (graphene), and examples include single-wall carbon nanotubes (SWCNTs) and multi-wall carbon nanotubes (MWCNTs). The conductive additive in the positive electrode active material layer of this embodiment preferably includes at least one selected from the group consisting of SWCNTs and MWCNTs, and more preferably includes MWCNTs. Furthermore, in addition to CNTs, carbon black may be used in combination to support the conductivity of the positive electrode active material layer.
[0039] In this embodiment, the content of the conductive additive in the positive electrode active material layer is preferably 0.05 parts by mass or more and 10.0 parts by mass or less, more preferably 0.1 parts by mass or more and 5.0 parts by mass or less, even more preferably 0.2 parts by mass or more and 2.5 parts by mass or less, and even more preferably 0.5 parts by mass or more and 2.0 parts by mass or less, when the total amount of the positive electrode active material layer is 100.0 parts by mass, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery. When carbon nanotubes are used alone or in combination with other conductive additives as a conductive additive, the content of carbon nanotubes in the positive electrode active material layer in this embodiment is preferably 0.01 parts by mass or more and 3.0 parts by mass or less, more preferably 0.03 parts by mass or more and 2.0 parts by mass or less, and even more preferably 0.05 parts by mass or more and 1.5 parts by mass or less, when the total amount of the positive electrode active material layer is 100.0 parts by mass, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery.
[0040] Examples of binders in the positive electrode active material layer of this embodiment include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyhexafluoropropylene (PHFP), polyvinyl fluoride (PVF), and VdF-hexafluoropropylene copolymers; polycarboxylic acid polymers such as poly(meth)acrylic acid; conductive polymers such as polyanilines, polythiophenes, polyacetylenes, and polypyrroles; synthetic rubbers such as styrene-butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile-butadiene rubber (NBR); and polysaccharides such as carboxymethylcellulose (CMC), xanthan gum, guar gum, and pectin. One of these may be used alone, or two or more may be used in combination. Among these, the binder in the positive electrode active material layer of this embodiment preferably comprises one or more selected from the group consisting of fluororesin, polycarboxylic acid polymer, and synthetic rubber, from the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, more preferably comprises one or more selected from the group consisting of polyvinylidene fluoride, polycarboxylic acid polymer, and styrene-butadiene rubber, and even more preferably comprises polyvinylidene fluoride.
[0041] From the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, the binder content in the positive electrode active material layer of this embodiment is preferably 0.05 parts by mass or more and 10.0 parts by mass or less, more preferably 0.1 parts by mass or more and 5.0 parts by mass or less, even more preferably 0.2 parts by mass or more and 2.5 parts by mass or less, and even more preferably 0.5 parts by mass or more and 2.0 parts by mass or less, when the total amount of the positive electrode active material layer is 100.0 parts by mass.
[0042] In addition, electrode additives commonly used for electrode formation, such as thickeners, dispersants, and stabilizers, can be appropriately used in the positive electrode active material layer.
[0043] From the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, the thickness of the positive electrode active material layer in this embodiment is preferably 10 μm to 250 μm, more preferably 20 μm to 200 μm, and even more preferably 50 μm to 150 μm.
[0044] From the viewpoint of further improving the battery performance of the resulting lithium-ion secondary battery, the density of the positive electrode active material layer in this embodiment is preferably 0.5 g / cm³. 3 More than 5.0g / cm 3 More preferably, 1.0 g / cm³ 3 More than 4.5g / cm 3 More preferably, 2.5 g / cm³ 3 More than 4.0g / cm 3 More preferably, 3.0 g / cm³ 3 More than 4.0g / cm 3 The following applies:
[0045] The positive electrode current collector layer of this embodiment includes, for example, one or more materials selected from the group consisting of aluminum, stainless steel, nickel, titanium, and alloys thereof. The shape of the positive electrode current collector layer may be, for example, foil, flat plate, or mesh. The thickness of the positive electrode current collector layer is not particularly limited, but is, for example, 1 μm or more and 50 μm or less.
[0046] <Lithium-ion rechargeable battery> The lithium-ion secondary battery of this embodiment is equipped with the positive electrode of this embodiment. Since the lithium-ion secondary battery of this embodiment is equipped with a positive electrode containing the positive electrode active material of this embodiment, gas generation can be suppressed.
[0047] The lithium-ion secondary battery of this embodiment will be described with reference to the figures. Figure 1 is a schematic cross-sectional view showing an example of the lithium-ion secondary battery of this embodiment. As shown in Figure 1, the lithium-ion secondary battery 10 of this embodiment comprises, for example, the positive electrode of this embodiment, an electrolyte layer, and a negative electrode containing a negative electrode active material. A separator 5 can also be provided between the positive electrode and the negative electrode. Multiple pairs of positive and negative electrodes can be provided.
[0048] The lithium-ion secondary battery 10 has a positive electrode comprising a positive electrode current collector 3 made of a metal such as aluminum foil and a positive electrode active material layer 1 containing a positive electrode active material provided thereon, and a negative electrode comprising a negative electrode current collector 4 made of a metal such as copper foil and a negative electrode active material layer 2 containing a negative electrode active material provided thereon. The positive electrode and the negative electrode are laminated via a separator 5 made of a nonwoven fabric or a polypropylene microporous film, for example, so that the positive electrode active material layer 1 and the negative electrode active material layer 2 face each other. This electrode pair is housed in a container formed of an outer casing 6, 7 made of an aluminum laminate film, for example. A positive electrode tab 9 is connected to the positive electrode current collector 3 and a negative electrode tab 8 is connected to the negative electrode current collector 4, and these tabs are led out of the container. An electrolyte is injected into the container and sealed. A structure in which a group of electrodes, each consisting of multiple laminated electrode pairs, is housed in the container is also possible.
[0049] The lithium-ion secondary battery 10 can be manufactured according to known methods. For electrodes, for example, laminates or wound bodies can be used. For the outer casing, metal casings or aluminum laminate casings can be used as appropriate. The shape of the battery may be any shape, such as coin type, button type, sheet type, cylindrical type, prismatic type, or flat type.
[0050] In the lithium-ion secondary battery of this embodiment, the negative electrode preferably comprises a negative electrode active material layer containing a negative electrode active material and a negative electrode current collector. The negative electrode active material layer of this embodiment preferably contains a negative electrode active material and a binder, and more preferably contains a negative electrode active material, a binder and a conductive additive.
[0051] In this embodiment, the negative electrode active material in the negative electrode active material layer preferably comprises one or more negative electrode active materials selected from the group consisting of carbon materials, lithium-based metal materials, Si-based materials, and conductive polymer materials, from the viewpoint of further reducing the amount of gas generated in the resulting lithium-ion secondary battery. More preferably, it comprises one or more negative electrode active materials selected from the group consisting of carbon materials and Si-based materials, and even more preferably, it comprises both Si-based materials and carbon materials.
[0052] The carbon material contained in the negative electrode active material of this embodiment includes, for example, graphite particles, hard carbon, soft carbon, carbon black, or any mixture thereof, and preferably includes graphite particles. Graphite particles can be obtained, for example, from Nippon Graphite Industries Co., Ltd., JFE Chemical Corporation, etc.
[0053] The Si-based material included in the negative electrode active material of this embodiment includes, for example, silicon oxide and Si-C composite particles containing silicon and carbon materials, and from the viewpoint of further improving the capacity retention rate, Si-C composite particles are preferred.
[0054] Silicon oxides can be obtained from sources such as Sigma-Aldrich, High Purity Chemical Laboratories, Kanto Chemical Co., Ltd., Fujifilm Wako Pure Chemical Industries Ltd., and Osaka Titanium.
[0055] The Si-C composite particles of this embodiment are particles in which the carbon material includes a porous carbon material, and silicon is present in at least a portion of the pores of the porous carbon material. In this embodiment, the method for producing Si-C composite particles is not particularly limited, but for example, a median diameter of 4.0 to 10.0 μm and a specific surface area of 1000 to 1800 m² may be used. 2 This material can be obtained by a manufacturing method in which porous carbon material is placed in a tubular furnace, the furnace is purged with argon gas, a mixed gas of silane gas containing 1-3 mol% silane gas and nitrogen gas is flowed into the tubular furnace at a flow rate of 250-350 sccm, and the process is carried out under conditions of 450-550°C, 700-800 Torr, and 90-150 minutes. Examples of porous carbon materials constituting the Si-C composite particles of this embodiment include activated carbon, aggregates of carbon fibers or carbon nanotubes, and carbon obtained by heat-treating resins or organic materials. Porous carbon materials can be produced by known manufacturing methods such as activated carbon production methods or by heat-treating polymers, but commercially available materials may also be purchased, and are not limited to these, as long as silicon can be generated or incorporated into the pores of the porous carbon.
[0056] In the lithium-ion secondary battery of this embodiment, the content of graphite particles in the negative electrode active material layer is W A The content of Si-C composite particles in the negative electrode active material layer is W B When each of these is done, W B W A The ratio W A / W B The value of is preferably 1.0 to 20.0, more preferably 2.0 to 15.0, even more preferably 2.5 to 10.0, even more preferably 2.8 to 8.0, even more preferably 3.0 to 5.5, and even more preferably 3.5 to 5.0, in order to further improve the battery performance of the resulting lithium-ion secondary battery.
[0057] In this embodiment, the content of the negative electrode active material in the negative electrode active material layer is preferably 50.0 parts by mass or more and 100.0 parts by mass or less, more preferably 75.0 parts by mass or more and 99.0 parts by mass or less, even more preferably 85.0 parts by mass or more and 98.5 parts by mass or less, even more preferably 90.0 parts by mass or more and 98.0 parts by mass or less, and even more preferably 95.0 parts by mass or more and 97.5 parts by mass or less, when the total amount of the negative electrode active material layer is 100.0 parts by mass, in order to further improve the battery performance of the resulting lithium-ion secondary battery.
[0058] Examples of conductive additives in the negative electrode active material layer of this embodiment include carbon fibers such as carbon nanofibers; carbon blacks such as acetylene black and Ketjen black; and carbon materials such as activated carbon, mesoporous carbon, fullerenes, and carbon nanotubes. One of these may be used alone, or two or more may be used in combination.
[0059] In this embodiment, the content of the conductive additive in the negative electrode active material layer is preferably 0.01 parts by mass or more and 5.0 parts by mass or less, more preferably 0.03 parts by mass or more and 3.0 parts by mass or less, even more preferably 0.05 parts by mass or more and 1.0 part by mass or less, and even more preferably 0.07 parts by mass or more and 0.5 parts by mass or less, when the total amount of the negative electrode active material layer is 100.0 parts by mass, in order to further improve the battery performance of the resulting lithium-ion secondary battery.
[0060] Examples of binders in the negative electrode active material layer of this embodiment include fluororesins such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinyl fluoride (PVF); polycarboxylic acid polymers such as poly(meth)acrylic acid; conductive polymers such as polyaniline, polythiophene, polyacetylene, and polypyrrole; synthetic rubbers such as styrene-butadiene rubber (SBR), butadiene rubber (BR), chloroprene rubber (CR), isoprene rubber (IR), and acrylonitrile-butadiene rubber (NBR); and polysaccharides such as carboxymethylcellulose (CMC), xanthan gum, guar gum, and pectin. One of these may be used alone, or two or more may be used in combination.
[0061] In this embodiment, the binder content in the negative electrode active material layer is preferably 0.1 parts by mass or more and 10.0 parts by mass or less, more preferably 1.0 parts by mass or more and 7.0 parts by mass or less, and even more preferably 2.0 parts by mass or more and 5.0 parts by mass or less, when the total amount of the negative electrode active material layer is 100.0 parts by mass, in order to further improve the battery performance of the resulting lithium-ion secondary battery.
[0062] The negative electrode current collector of this embodiment includes, for example, one or more materials selected from the group consisting of copper, stainless steel, nickel, titanium, and alloys thereof. The shape of the negative electrode current collector may be, for example, foil, flat plate, or mesh. The thickness of the negative electrode current collector is not particularly limited, but is, for example, 1 μm or more and 50 μm or less.
[0063] The electrolyte layer in this embodiment is a layer positioned between the positive electrode and the negative electrode. The electrolyte layer includes a separator and an electrolyte solution, and examples include a porous separator impregnated with a non-aqueous electrolyte solution, or a solid electrolyte layer.
[0064] Examples of electrolytes in this embodiment include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), and butylene carbonate (BC); linear carbonates such as ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and dipropyl carbonate (DPC); aliphatic carboxylic acid esters; γ-lactones such as γ-butyrolactone; linear ethers; and cyclic ethers, in which lithium salts such as lithium hexafluoride phosphate (LiPF6), lithium borofluoride (LiBF4), LiFSI, and lithium perchlorate (LiClO4) are dissolved. The organic solvent may be used alone or in combination of two or more.
[0065] The separator of this embodiment mainly consists of a porous membrane, woven fabric, nonwoven fabric, etc., made of resin, and as the resin component, for example, polyolefin resins such as polypropylene and polyethylene, polyester resins, acrylic resins, styrene resins, or nylon resins can be used. In addition, if necessary, a layer containing inorganic particles may be formed in the separator, and examples of inorganic particles include insulating oxides, nitrides, sulfides, carbides, etc.
[0066] As the outer casing of this embodiment, a case or can made of a flexible film can be used, and from the viewpoint of reducing the weight of the battery, it is preferable to use a flexible film. The flexible film can be one in which a resin layer is provided on both the front and back surfaces of a metal base layer. The metal layer can be selected to have barrier properties such as preventing leakage of electrolyte and intrusion of moisture from the outside, and can be made of aluminum, stainless steel, etc. At least one surface of the metal layer is provided with a heat-sealable resin layer, such as a modified polyolefin. The outer casing is formed by facing the heat-sealable resin layers of the flexible film toward each other and heat-sealing the area around the part that houses the electrode laminate. A resin layer such as a nylon film or polyester film can be provided on the surface of the outer casing opposite to the surface on which the heat-sealable resin layer is formed.
[0067] <Lithium-ion secondary battery module> The lithium-ion secondary battery module of this embodiment comprises the lithium-ion secondary battery of this embodiment. Since the lithium-ion secondary battery of this embodiment can suppress gas generation, the lithium-ion secondary battery module of this embodiment can suppress gas generation.
[0068] The lithium-ion secondary battery module of this embodiment preferably includes two or more lithium-ion secondary batteries of this embodiment connected in series or in parallel. The lithium-ion secondary battery module of this embodiment more preferably includes a housing capable of housing two or more lithium-ion secondary batteries of this embodiment connected in series or in parallel. The lithium-ion secondary battery module of this embodiment more preferably includes one or more selected from the group consisting of a protection circuit to protect the lithium-ion secondary batteries from overcurrent, a balance circuit to equalize the voltage between the electrodes of the lithium-ion secondary batteries, a controller to control the lithium-ion secondary batteries, a cooler capable of cooling the lithium-ion secondary batteries, and a heater capable of heating the lithium-ion secondary batteries.
[0069] The lithium-ion secondary battery module of this embodiment can be used in a battery system comprising multiple electrically connected lithium-ion secondary battery modules and a battery control system. Examples of battery systems include battery packs, stationary battery systems, automotive power battery systems, automotive auxiliary battery systems, and emergency power supply battery systems.
[0070] The embodiments of the present invention have been described above, but these are merely examples, and various other configurations can also be adopted.
[0071] It should be noted that the present invention is not limited to the embodiments described above, and any modifications, improvements, etc., that can achieve the objectives of the present invention are included in the present invention. [Examples]
[0072] The present invention will be specifically described below with reference to examples, but the present invention is not limited thereto. Details of the manufacturing methods for the positive electrode active materials in Examples 1 and 2 and Comparative Example 1 are as follows.
[0073] <Method for preparing positive electrode active material> (Example 1) Nickel sulfate, cobalt sulfate, manganese sulfate, sodium hydroxide, ammonia water, and deionized water are placed in a batch-type reactor, and nickel-cobalt-manganese composite hydroxide particles (Ni) are formed by coprecipitation. 0.94 Co 0.05 Mn 0.01 (OH)2) was prepared. Next, the obtained nickel-cobalt-manganese composite hydroxide particles were mixed with LiOH to obtain a mixture in which the molar ratio of lithium to the transition metal (Li / (Ni+Co+Mn)) was 1.05. The obtained mixture was calcined in an oxygen atmosphere at 600°C for 20 hours (hereinafter referred to as the calcination process). Next, the mixture obtained in the calcination process was pulverized in a grinder, and then further calcined at 800°C for 20 hours under an oxygen atmosphere. Next, the resulting calcined powder was ground in a wet ball mill for 8 hours, and then classified using a sieve with a mesh size of 20 μm to obtain lithium-nickel-cobalt-manganese composite oxide (LiNi 0.94 Co 0.05 Mn 0.01 We obtained single-crystal particles composed of O2, in which the aggregation of primary particles was suppressed. A mixture was prepared by mixing single crystal particles composed of the manufactured lithium-nickel-cobalt-manganese composite oxide with powdered Co(OH)2 in a molar ratio of 1:0.01. The resulting mixture was heat-treated at 700°C for 6 hours under an oxygen atmosphere to produce the positive electrode active material of Example 1. Here, in the positive electrode active material, the portion other than the Co coating layer is called the core.
[0074] (Example 2) The composition of nickel-cobalt-manganese composite hydroxide particles is Ni 0.90 Co 0.05 Mn 0.05 The positive electrode active material was prepared in the same manner as in Example 1, except that (OH)2 was used and the grinding time in the wet ball mill was set to 7 hours.
[0075] (Comparative Example 1) The composition of nickel-cobalt-manganese composite hydroxide particles is Ni 0.91 Co 0.07 Mn 0.02 The positive electrode active material was prepared in the same manner as in Example 1, except that (OH)2 was used and the grinding time in the wet ball mill was set to 4 hours.
[0076] <Number of microcracks in the positive electrode active material after compression> The number of microcracks in the positive electrode active material of each example and comparative example was measured after compression according to the method described below. The results are shown in Table 1. (method) Two g of the positive electrode active material from each example and comparative example was placed in a circular mold with a diameter of 1.5 cm (LaboPress, manufactured by Labonect), and the density was 3.7 g / cm³. 3 It was compressed to achieve this. The number of microcracks was measured by visually counting the number of microcracks within a 10 μm × 10 μm area from images obtained by SEM observation at a magnification of 5000x. Measurements were taken at 10 different locations, and the average of the microcrack counts from these 10 locations was used as the number of microcracks after compression.
[0077] <Number of nanoparticles after compression of positive electrode active material> The number of nanoparticles with a maximum diameter of 10 nm to 50 nm was measured after compressing the positive electrode active material of each example and comparative example according to the method described below. The results are shown in Table 1. (method) Two g of the positive electrode active material from each example and comparative example was placed in a circular mold with a diameter of 1.5 cm (LaboPress, manufactured by Labonect), and the density was 3.7 g / cm³. 3 It was compressed to achieve this. The number of nanoparticles with a maximum diameter between 10 nm and 50 nm was measured by visually counting nanoparticles with a maximum diameter between 10 nm and 50 nm attached to the surface of the positive electrode active material within a 10 μm × 10 μm area, based on images obtained by SEM observation at a magnification of 5000x. Measurements were performed at 10 different locations, and the average number of nanoparticles with a maximum diameter between 10 nm and 50 nm at these 10 locations was used as the number of nanoparticles after compression.
[0078] <Measurement of particle size of positive electrode active material> From the volume frequency particle size distribution measured by laser diffraction scattering using a laser diffraction particle size distribution analyzer (Horiba, LA960V2), the particle size D at which the cumulative values are 10%, 50%, and 90% is determined. 10 , average particle diameter D 50 , particle size D 90 The following was determined. Here, the positive electrode active material was suspended in a dispersion medium (0.1% by mass sodium hexametaphosphate aqueous solution), ultrasonically dispersed, and then measured. Five measurements were taken, and the average value was adopted for each. From the obtained values, (D 90 -D 10 ) / D 50 The value was calculated. The results are shown in Table 1.
[0079] <Fabrication of the positive electrode> For each example and comparative example, the positive electrode active material, conductive additive, and binder were mixed in the proportions shown in Table 1, and an appropriate amount of water was added to prepare a positive electrode active material slurry. Next, each positive electrode active material slurry was applied to a 12 μm thick aluminum foil, which served as the positive electrode current collector, with an initial charge capacity of 4.2 mAh / cm² per unit area. 2 After coating with an amount such that the desired result was obtained, the material was dried to obtain a positive electrode laminate. Next, using a roll press machine, the positive electrode laminate was processed so that the density of the positive electrode active material layer was 3.7 g / cm³. 3 The positive electrodes for each embodiment and comparative example were obtained by pressing with a pressure such that the electrodes were pressed.
[0080] <Fabrication of the negative electrode> A mixture consisting of 96.8 parts by mass of graphite and Si-C composite particles, 0.2 parts by mass of single-walled carbon nanotubes, and 3 parts by mass of polyacrylic acid was prepared by adding an appropriate amount of water to the mixture to prepare a negative electrode active material slurry. Next, the negative electrode active material slurry was applied to a 10 μm thick copper foil, which served as the negative electrode current collector, to achieve an initial charge capacity of 4.3 mAh / cm² per unit area. 2 After coating with an amount such that the following was achieved, the material was dried to obtain a negative electrode laminate. Next, using a roll press, the negative electrode laminate was processed so that the density of the negative electrode active material layer was 1.65 g / cm³. 3 The negative electrode was obtained by pressing with a pressure such that the following occurred.
[0081] <Preparation of non-aqueous electrolyte> The non-aqueous electrolyte was prepared by mixing an organic solvent with a supporting salt. The cyclic carbonate ethylene carbonate and the linear carbonate ethylmethyl carbonate were adjusted to a volume ratio of 3 / 7. Furthermore, lithium hexafluoride phosphate (LiPF6) (concentration: 1.2 mol / L) was used as the supporting salt, and fluoroethylene carbonate (concentration relative to the organic solvent: 6% by mass) was used as an additive.
[0082] <Manufacturing of lithium-ion secondary batteries> The negative electrode and the positive electrode of each example and comparative example were cut to 3 cm x 3 cm and placed opposite each other with a separator in between to create an electrode laminate. A 10 μm thick microporous polyethylene film coated with ceramic on both sides was used as the separator. Next, the electrode laminate and the non-aqueous electrolyte were placed inside a laminate casing molded from a film mainly composed of aluminum, and positive electrode tabs and negative electrode tabs were connected to the negative electrode and positive electrode, respectively. The lithium-ion secondary batteries of each example and comparative example were then fabricated by sealing the periphery of the laminate casing. Here, one end of the positive electrode tab is connected to the positive electrode and the other end is led out of the casing, and one end of the negative electrode tab is connected to the negative electrode and the other end is led out of the casing.
[0083] <Measurement of volume change rate before and after cycle testing> The lithium-ion secondary batteries of each example and comparative example were placed in a constant temperature bath at 45°C and charged at 30mA. After the upper voltage limit reached 4.2V, charging was continued at a constant voltage until the total charging time was 2.5 hours. Next, they were discharged at a constant current of 30mA until the lower voltage limit reached 2.5V. This charge-discharge cycle was then repeated 750 times. The volume of the lithium-ion secondary battery after 2 charge-discharge cycles and the volume of the lithium-ion secondary battery after 750 charge-discharge cycles were measured, and the volume change rate after charge-discharge for each example and comparative example was calculated using the following formula. The results are shown in Table 1. The volume of the lithium-ion secondary battery was measured using the Archimedes method. (Percentage change in volume before and after cycle testing) [%] = 100 × (Volume of lithium-ion secondary battery after 750 charge / discharge cycles) / (Volume of lithium-ion secondary battery after 2 charge / discharge cycles)
[0084] [Table 1]
[0085] It is known that in lithium-nickel-cobalt-manganese composite oxides, the higher the nickel content, the greater the amount of gas generated after the cycle test, and the greater the rate of volume change of the lithium-ion secondary battery. However, as shown in the results of Examples 1 and 2, even with a high nickel content of 90 mol% or more, if the number of microcracks after compression is 2.0 or less, the rate of volume change of the lithium-ion secondary battery before and after the cycle test can be reduced, meaning that the amount of gas generated after the cycle test can be suppressed. Here, nickel content refers to the nickel content (mol%) when the total amount of metal elements other than lithium in the lithium-nickel-cobalt-manganese composite oxide is set to 100 mol%.
[0086] Details of each component in Table 1 are as follows: <Binder> • PVDF (polyvinylidene fluoride, manufactured by Solvay)
[0087] <Conductive additive> • MWCNT (Multi-Walled Carbon Nanotube, Aspect Ratio: 100, Specific Surface Area: 300 m²) 2 / g)
[0088] <Negative electrode active material> Si-C composite particles: Graphite = 17.5:82.5 (mass ratio) (Fabrication of Si-C composite particles) Porous carbon material (D 50 :4.8μm, specific surface area: 1678m 2 The material ( / g) was placed in a tubular furnace, the furnace was purged with argon gas, and then a mixed gas of 2 mol% silane gas and 98 mol% nitrogen gas was flowed into the furnace at a flow rate of 300 sccm. The process was carried out under conditions of 500°C, 760 Torr, and 120 minutes. The product was then cooled to room temperature to obtain Si-C composite particles. Cross-sections of the obtained Si-C composite particles were analyzed using a scanning electron microscope (Hitachi High-Tech Corporation, SU3500), an energy-dispersive X-ray spectroscopy detector (Oxford Instruments, Ultim Max 40), and image analysis software (Oxford Instruments, Aztec). Secondary electrons were selected as the target of detection, and elemental mapping of silicon and carbon was performed under the conditions of an acceleration voltage of 3kV, 20 mapping integrations, and a magnification of 3000x. This confirmed that the Si-C composite particles contain silicon, and that silicon is present in at least a portion of the pores of the porous carbon material within the Si-C composite particles.
[0089] (Graphite mixing ratio) Artificial graphite containing amorphous carbon on the surface: Artificial graphite without amorphous carbon on the surface = 1:1 (mass ratio) • Median diameter D of artificial graphite containing amorphous carbon on its surface 50 :17μm, specific surface area: 1.3m 2 / g • Median diameter D of artificial graphite that does not contain amorphous carbon on its surface 50 :17μm, specific surface area: 2.2m 2 / g [Explanation of Symbols]
[0090] 1 Cathode active material layer 2 Negative electrode active material layer 3 Positive electrode current collector 4 Negative electrode current collector 5 Separators 6. Exterior 7. Exterior 8 Negative Electrode Tabs 9 Positive Tab 10 Lithium-ion rechargeable batteries
Claims
1. A positive electrode active material for lithium-ion secondary batteries, A positive electrode active material having 2.0 or fewer microcracks after compression, as measured by the following method (Method 1). (Method 1) The positive electrode active material is placed in a mold, and the density is 3.7 g / cm³. 3 The material is compressed to the following state. The compressed positive electrode active material is observed by SEM at a magnification of 5000x, and the number of microcracks within a 10 μm × 10 μm area is measured from the image obtained. The number of microcracks within a 10 μm × 10 μm area is measured at 10 different locations on the compressed positive electrode active material, and the average value of the microcrack counts at the 10 locations is taken as the number of microcracks after compression.
2. The positive electrode active material according to claim 1, wherein the number of nanoparticles after compression of the positive electrode active material, as measured by the following method (method 2), is 10.0 or less. (Method 2) The positive electrode active material is placed in a mold, and the density is 3.7 g / cm³. 3 The material is compressed to the following state. The compressed positive electrode active material is observed by SEM at a magnification of 5000x, and the number of nanoparticles with a maximum diameter of 10 nm to 50 nm attached to the surface of the positive electrode active material within a range of 10 μm × 10 μm is measured from the image obtained. The number of nanoparticles within a range of 10 μm × 10 μm is measured at 10 different locations on the compressed positive electrode active material, and the average value of the number of nanoparticles at the 10 locations is taken as the number of nanoparticles after compression.
3. The average particle size D of the volume-based particle size distribution of the positive electrode active material as measured by laser diffraction scattering particle size distribution analysis. 50 The positive electrode active material according to claim 1 or 2, wherein the particle size is 0.5 μm or more and 15.0 μm or less.
4. A particle diameter D at which the cumulative value in the volume-based particle size distribution of the positive electrode active material determined by a laser diffraction-scattering particle size distribution measurement method is 10% 10 , a particle diameter D at which the cumulative value is 90% 90 and an average particle diameter D 50 calculated as (D 90 -D 10 ) / D 50 has a value of 0.50 or more and 2.00 or less, the positive electrode active material according to any one of claims 1 to 3.
5. The particle size D of the positive electrode active material at which the cumulative value of the volume-based particle size distribution measured by laser diffraction scattering particle size distribution analysis is 10% 10 The positive electrode active material according to any one of claims 1 to 4, wherein the particle size is 0.1 μm or more and 10.0 μm or less.
6. The particle size D of the positive electrode active material at which the cumulative value of the volume-based particle size distribution measured by laser diffraction scattering particle size distribution analysis is 90% 90 The positive electrode active material according to any one of claims 1 to 5, wherein the particle size is 1.0 μm or more and 25.0 μm or less.
7. A positive electrode active material according to any one of claims 1 to 6, comprising single crystal particles composed of lithium composite oxide (X).
8. The positive electrode active material according to claim 7, wherein the lithium composite oxide (X) comprises one or more composite oxides selected from the group consisting of lithium-nickel composite oxides, lithium-cobalt composite oxides, lithium-nickel-aluminum composite oxides, and lithium-nickel-cobalt-manganese composite oxides.
9. The positive electrode active material according to claim 7 or 8, wherein the lithium composite oxide (X) includes a lithium-nickel-cobalt-manganese composite oxide.
10. The positive electrode active material according to any one of claims 7 to 9, wherein when the total amount of metallic elements other than lithium contained in the lithium composite oxide (X) is taken as 100 mol%, the nickel content is 80 mol% or more.
11. A positive electrode active material according to any one of claims 1 to 10, wherein the volume change rate by the method described below (Method 3) is 120% or less. (Method 3) A mixture consisting of 97.5 parts by mass of the positive electrode active material, 1.0 part by mass of MWCNT (multi-walled carbon nanotube), and 1.5 parts by mass of PVDF (polyvinylidene fluoride) is to be mixed with an appropriate amount of water to prepare a positive electrode active material slurry. Next, the positive electrode active material slurry is applied to aluminum foil, which is the positive electrode current collector, to an initial charge capacity of 4.2 mAh / cm² per unit area. 2 After applying the material in an amount that results in the above, it is dried to obtain a positive electrode laminate. Next, using a roll press machine, the positive electrode laminate is processed so that the density of the positive electrode active material layer is 3.7 g / cm³. 3 The positive electrode is obtained by pressing with a pressure such that the positive electrode and the negative electrode containing a mixture of graphite and Si-C composite particles are arranged opposite each other via a polyethylene separator. This electrode laminate and a non-aqueous electrolyte are placed inside a laminate casing molded from a film mainly composed of aluminum. A positive electrode tab and a negative electrode tab are connected to the negative electrode and the positive electrode, respectively, and the casing is sealed to produce a lithium-ion secondary battery. The obtained lithium-ion secondary battery is placed in a constant temperature bath at 45°C and charged at 30mA. After the upper limit voltage reaches 4.2V, it is charged at a constant voltage until the total charging time is 2.5 hours. Next, it is discharged at a constant current of 30mA until the lower limit voltage reaches 2.5V. This charge-discharge cycle is repeated 750 times, and the volume change rate is calculated from the volume of the lithium-ion secondary battery after 750 charge-discharge cycles and the volume of the lithium-ion secondary battery after 2 charge-discharge cycles.
12. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 11.
13. A lithium-ion secondary battery comprising the positive electrode described in claim 12.
14. A lithium-ion secondary battery module comprising the lithium-ion secondary battery described in claim 13.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery, method for producing the same, and lithium secondary battery including the same
JP2023551231A